A world of hurt: failure to achieve treatment goals in patients with gout requires a paradigm shift. Issue 1 (2nd January 2016) - Khanna, Puja; Khanna, Dinesh; Storgard, Chris; Baumgartner, Scott; Morlock, Robert
Abstract: Background : Gout continues to be underdiagnosed and poorly managed despite the potential for cure. US and European management guidelines recommend treating to target serum urate (sUA) levels of <6 mg/dL (or <5 mg/dL to durably improve severe symptoms), with use of regular sUA monitoring, but studies suggest relatively poor adherence to these recommendations. This study investigates the real-world state of gout management in the United States by describing the characteristics of a large patient population treated in primary care and rheumatology settings. Methods : A retrospective chart audit, conducted among 124 primary care physicians and 125 rheumatologists, included 1245 patients with gout. Physicians completed structured case report forms capturing 12 months of sUA laboratory values, flare counts, comorbidities, types and doses of treatment, treatment duration, diagnosis date, physician specialty and socio-demographic factors. Focusing on the xanthine oxidase inhibitors ( n = 858), descriptive statistics and multivariate models characterized relationships between patient characteristics, disease control, and treatment. Results : Only 83 (11%) patients achieved disease control, defined as a 12-month average sUA ≤6 mg/dL, no flares, and no tophi. Patients with greatest disease severity (defined as sUA >6 mg/dL, ≥2 flares per year, and tophi) were more likely to have kidney disease and other comorbidities. In a multivariate model, predictors of more severe gout were rheumatologist (vs primary care) management, febuxostat (vs allopurinol) use and presence of comorbid conditions. Conclusion : Our findings confirm the inadequacy of gout management in the real-world setting. Regular monitoring, including sUA measurement as recommended in guidelines, is important to assess gout control. Our analyses also demonstrate that patients with more severe gout are more likely to have comorbid conditions, be treated by a specialist and use newer therapies.